High genetic drift in endangered northern peripheral populations of the Behr's hairstreak butterfly (Satyrium behrii). Issue 3 (27th December 2020) - Keyghobadi, Nusha; Crawford, Lindsay A.; Desjardins, Sylvie
Abstract: The persistence and adaptation of leading‐edge peripheral populations may be critical for allowing species to shift their range limits under climate change. However, peripheral populations are potentially vulnerable to genetic, demographic, and environmental stochasticity. Here, we characterise genetic variation across space and among years in northern peripheral populations of the Behr's hairstreak butterfly in British Columbia, Canada. This butterfly is dependent on antelope‐brush ecosystems that are threatened in this part of the world and is federally listed as Endangered in Canada. Using a large panel of amplified fragment length polymorphism (AFLP) genetic markers, we found low diversity in these populations. We also detected a high degree of year‐to‐year variation in allele frequencies, resulting in low effective population size estimates. Our findings suggest that Canadian populations of the Behr's hairstreak experience high genetic drift and may be vulnerable to genetic stochasticity. Unstable demography, low effective population size, and low genetic diversity in these populations could impede their adaptation to rapidly changing environmental conditions and contribute to a contraction of the species' range under climate change. Abstract : We characterised genetic variation among sites and across years in endangered northern peripheral populations of the Behr's hairstreak butterfly in British Columbia, Canada. We found low diversity and a high degree of year‐to‐year variation in allele frequencies, resulting in low effective population size estimates. Our findings suggest that Canadian populations of the Behr's hairstreak experience high genetic drift and may be vulnerable to genetic stochasticity.